Pola Konsumsi merupakan Faktor yang Paling Dominan Berpengaruh terhadap Kejadian Infeksi Oportunistik pada ODHA di RSUP Dr. Kariadi Semarang - Sumiyati, Sumiyati; Widjanarko, Bagoes (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2015)
ABSTRACTFood Intake is The Most Dominant Factors Influencing Toward Opportunistic Infections On People With HIV/AIDS At Dr. Kariadi Hospital Semarang; The infection disease of HIV and AIDS is the main cause of death around the world today. One of the causes of high mortality and disability is opportunistic infection. The number of deaths recorded as many as 68 (73.9%) caused by opportunistic infections at Dr. Kariadi Hospital in 2014. The objective of this study is to analyze the factors influencing for the incidence of opportunistic infections on people with HIV/AIDS at Dr Kariad Hospital Semarangi. This study is quantitative research with cross sectional design. Sample is HIV / AIDS patients who visited at Dr KariadiHospital Semarang. The systematic random sampling technique is used in this study. The amount of sample is 82 people from 523of popolations. Data has collected by interview and observation. The results of univariate analysis illustrates that respondents with HIV / AIDS who have 53.7% Opportunistic Infections are most opportunistic infections are tuberculosis amounted to 31.82%. Results of bivariate analysis using statistical test Chi-Square shows there are nine variables significantly associated, namely the control examination, ARV adherence, food intake, food safety, personal hygiene, activity patterns, family support, peer support, and the support of a case manager. The most dominant variable is the effect of nutrient intake (OR = 7.477).Keywords: HIV / AIDS, Opportunistic Infections, Behavior